IMF Research Bulletin June 2013. (IMF Research Bulletin; IMF Research Bulletin ;, 2013)
The June issue of the IMF Research Bulletin looks at the role of IMF programs and capacity building in fostering structural reforms and the economics of Arab countries undergoing political transitions. The Q and A analyzes the neutral interest rate through the experiences of several Latin American countries. The Research Bulletin also includes its regular features: a listing of IMF Working Papers and Staff Discussion Notes, information on the forthcoming IMF Economic Review and the Fourteenth Jacques Polack Annual Research Conference, and recommended readings from IMF Publications.